1997
DOI: 10.1007/s004670050229
|View full text |Cite
|
Sign up to set email alerts
|

Possible person-to-person transmission of Escherichia coli O111 - associated hemolytic uremic syndrome

Abstract: Over a 3-month period, ten children (aged 1-13 years) from a 15-km radius in southern Picardy developed typical D+ hemolytic uremic syndrome (HUS). Polymerase chain reaction, using two pairs of verocytotoxin 1-(VT1) and VT2-specific oligonucleotide primers and an internal control was used to detect VT genes directly from stools samples. VT2 gene was detected in seven of nine patients' stools and in 5 of 14 contacts' stool samples. A VT2-producing Escherichia coli (VTEC) O111 was isolated from five of nine chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 22 publications
2
42
1
2
Order By: Relevance
“…A strain of serotype O111:H2 [14] caused a small outbreak of HUS in France in 1995, but the episode involved children, as is typical for STEC/VTEC [15]. As in the present outbreak in Germany, the association of the French strains with severe disease (HUS) supports the view that this unusual combination of virulence factors might confer a very high degree of virulence.…”
Section: Screening For the Outbreak Strainsupporting
confidence: 66%
“…A strain of serotype O111:H2 [14] caused a small outbreak of HUS in France in 1995, but the episode involved children, as is typical for STEC/VTEC [15]. As in the present outbreak in Germany, the association of the French strains with severe disease (HUS) supports the view that this unusual combination of virulence factors might confer a very high degree of virulence.…”
Section: Screening For the Outbreak Strainsupporting
confidence: 66%
“…5,6 Although gastrointestinal symptoms in family contacts were less common in our study, it has been reported that approximately 40% of household contacts of children with HUS have the free toxin identified in their feces. 6,7 HUS outbreaks may start due to simultaneous exposure of several individuals to a common food source, although secondary person-toperson transmission may occur within small communities or families.…”
Section: Discussioncontrasting
confidence: 49%
“…5 It has been described that family members who come in contact with children with typical HUS commonly have STEC colonization, and Shiga toxin has been frequently identified in the members of the same family. 6,7 The development and severity of person-to-person transmission may also depend on other factors, such as the amount of inoculum ingested and individual susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…Although this prevalence is relatively low, it should be pointed out that serogroup O111 has been involved in most non-O157 STEC infections (2). Besides, STEC O111 has been reported as responsible for outbreaks (6,8,9,23,37) and also sporadic cases (15,18,19,46). STEC strains carrying the eae gene are considered more virulent for humans than strains lacking eae (1).…”
Section: Resultsmentioning
confidence: 99%